UPLC-ESI-MS/MS-based widely targeted metabolomics reveals differences in metabolite composition among four Ganoderma species - Wei-Ye, Liu; Hong-Bo, Guo; Rui-Heng, Yang; Ai-Guo, Xu; Jia-Chen, Zhao; Zhao-Qian, Yang; Wen-Jun, Han; Xiao-Dan, Yu (Frontiers in Nutrition, 2024)
The Chinese name 'Lingzhi' refers to Ganoderma genus, which are increasingly used in the food and medical industries. Ganoderma species are often used interchangeably since the differences in their composition are not known. To find compositional metabolite differences among Ganoderma species, we conducted a widely targeted metabolomics analysis of four commonly used edible and medicinal Ganoderma species based on ultra performance liquid chromatography-electrospray ionizationtandem mass spectrometry. Through pairwise comparisons, we identified 575-764 significant differential metabolites among the species, most of which exhibited large fold differences. We screened and analyzed the composition and functionality of the advantageous metabolites in each species. Ganoderma lingzhi advantageous metabolites were mostly related to amino acids and derivatives, as well as terpenes, G. sinense to terpenes, and G. leucocontextum and G. tsugae to nucleotides and derivatives, alkaloids, and lipids. Network pharmacological analysis showed that SRC, GAPDH, TNF, and AKT1 were the key targets of high-degree advantage metabolites among the four Ganoderma species. Analysis of Gene Ontology and Kyoto Encyclopedia of Genes and Genomes demonstrated that the advantage metabolites in the four Ganoderma species may regulate and participate in signaling pathways associated with diverse cancers, Alzheimer's disease, and diabetes. Our findings contribute to more targeted development of Ganoderma products in the food and medical industries.